(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the semantic content of the associates on German-word-stimulus Überraschung surprise is obtained by directional associative experiment. The dominating importance of the test words as a nuclear base. Proved, that the semantics associates as linguistic phenomenon outlined formula «image and language level».